Concept of Khidmah from Syed Muhammad Naquib Al-Attas in Indonesian Islamic Higher Education - Saleh, Akhmad Hasan (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2023)
Prof. Naquib Al-Attas that the servant is obliged to perform service (khidmah) to Allah SWT. With this practice of khidmah, humans are called 'abd (servants). The practice of this khidmah is with worship, namely doing something that is ordered and living according to His rules. So, the meaning of din has four dimensions, namely indebtedness, surrender, the power of law, and natural tendencies. In many discussions about khidmah, it is only interpreted narrowly, namely only in the field of education, especially education in the life of Islamic boarding schools. This dissertation research proposal analyzes the concept of khidmah in a more comprehensive dimension and will contribute to the epistemology of Islamic psychology, tasawuf, and philosophy of Islamic education. This is at the same time novelty and will contribute to the study of thought, because this research will provide novelty in which the study of the concept of khidmah is comprehensive and philosophical. Because most khidmah studies are only partial in one scientific discipline, this dissertation will examine it philosophically (evidence gap and knowledge gap). This research is one of the few studies that conducts a philosophical study of the concept of khidmah and its contribution to the epistemology tasawwuf and Islamic philosophy of education.